FD-method for solving the nonlinear Klein–Gordon equation - Dragunov, D.V.; Makarov, V.L.; Sember, D.A. (Український математичний журнал, 2012)
We propose a functional discrete method for solving the Goursat problem for the nonlinear Klein–Gordon equation. Sufficient conditions for the superexponential convergence of this method are established. The obtained theoretical results are illustrated by a numerical example. Запропоновано функцiонально-дискретний метод розв’язування задачi Гурса для нелiнiйного рiвняння Кляйна – Гордона. Отримано достатнi умови, якi забезпечують суперекспоненцiальну швидкiсть збiжностi методу. Одержанi теоретичнi результати проiлюстровано на числовому прикладi.